The Effect of Landscaping and Building Facades on Perceptual-Behavioral Features of Citizens - Azma, Sara; Katanchi, Roxana (Journal of History Culture and Art Research, 2017)
Objective: Perception could provide the first or the most fundamental layer for recognition and hence, studying it should be prior to any other layer like layers of cultural world and especially, the real world. One of the categories, in which cognition becomes important, is the urban landscape and its designation to improve perceptual perceptions of audiences to enhance items such as sense of belonging and recognition of space and orientation. Therefore, the main purpose of this study is to investigate physical factors affecting urban bodies and its impact on perception and behavior of citizens and considering the gap in this field. Method: The method used in this study is interpretive and in form of qualitative analysis of available references on urban landscape and perception of citizens. The data collected through library research. The procedure is based on classification and content analysis in this study. Results: Landscaping and city walls could lead to emergence of perceptions such as perception of attractiveness and emotions of space, perception of identity and sense of belonging, perception of useful information, perception of hidden order and reagent of life stream, living at the streets, explicit transfer of performance message and perception of urban diversity in citizens. Conclusion: The results obtained from this study could lead to recognizing the relationship between designation and environmental psychology in designing urban landscape and desirable perception of citizens about the environment and the interaction between designation strategies in designing the facade that could finally lead to promotion of quality of the environment and mental comfort and satisfaction of citizens.